Climate-growth relationships of Norway Spruce and silver fir in primary forests of the Croatian Dinaric mountains - Begović, Krešimir; Rydval, Miloš; Mikac, Stjepan; Čupić, Stipan; Svobodova, Kristyna; Mikoláš, Martin; Kozák, Daniel; Kameniar, Ondrej; Frankovič, Michal; Pavlin, Jakob; Langbehn, Thomas; Svoboda, Miroslav (Agricultural and forest meteorology, 2020)
•Growth limited by high summer temperatures and water availability in the Dinaric MTS.•Earlywood blue intensity contains a stronger recent drought signal than ring width.•Spruce TRW response is stronger than in fir, but similar in EWBI of both species.•Recent spruce growth decline linked to increasing summer temperature and drought.•Ongoing climate change may have a strong impact on vitality and forest development. The past century has witnessed a global trend of increasing green house gas emissions, causing a rise in temperatures, changing hydroclimatic patterns and increasing occurrence of climatic extremes. Despite their importance for environmental conservation, scientific research and forest management, primary montane forests of the Dinaric Mts remain insufficiently studied. In this study, we examined the relationship between climate and growth of Norway spruce (Picea abies (L.) H. Karst.) and silver fir (Abies alba Mill.) in the primary forests of Smrčeve doline, located in Northern Velebit National Park, Croatia. Using dendrochronological methods, the temporal relationships between tree ring width (TRW) and blue intensity (BI) were assessed over the 1901–2014 interval, in relation to instrumental climatic data, including temperature, precipitation and self‐calibrating Palmer Drought Severity Index (scPDSI). TRW and earlywood BI (EWBI) chronologies of both species exhibited a clear negative response to summer temperatures, while also showing a positive relationship with summer precipitation and moisture, implying that tree growth in the region is water-limited. Generally, correlation values of EWBI were stronger compared to the TRW chronologies. Although both species showed a degree of common growth response to climatic extremes, the strength of correlations with the most responsive climatic variables was temporally unstable and showed considerable variability in both tree ring parameters. The observed differential response of the two species to climate indicates that the anticipated increase in dry conditions due to climate change could potentially alter the future development and composition of these primary forests by shifting competitive pressures in favor of silver fir. Increasing drought stress around the Mediterranean could have major negative implications for these water-limited primary forests.